How behavioural science can contribute to health partnerships: the case of The Change Exchange - Lucie M.T. Byrne-Davis; Eleanor R. Bull; Amy Burton; Nimarta Dharni; Fiona Gillison; Wendy Maltinsky; Corina Mason; Nisha Sharma; Christopher J. Armitage; Marie Johnston; Ged J. Byrne; Jo K. Hart (BMC, 2017)
Abstract Background Health partnerships often use health professional training to change practice with the aim of improving quality of care. Interventions to change practice can learn from behavioural science and focus not only on improving the competence and capability of health professionals but also their opportunity and motivation to make changes in practice. We describe a project that used behavioural scientist volunteers to enable health partnerships to understand and use the theories, techniques and assessments of behavioural science. Case studies This paper outlines how The Change Exchange, a collective of volunteer behavioural scientists, worked with health partnerships to strengthen their projects by translating behavioural science in situ. We describe three case studies in which behavioural scientists, embedded in health partnerships in Uganda, Sierra Leone and Mozambique, explored the behaviour change techniques used by educators, supported knowledge and skill development in behaviour change, monitored the impact of projects on psychological determinants of behaviour and made recommendations for future project developments. Discussion Challenges in the work included having time and space for behavioural science in already very busy health partnership schedules and the difficulties in using certain methods in other cultures. Future work could explore other modes of translation and further develop methods to make them more culturally applicable. Conclusion Behavioural scientists could translate behavioural science which was understood and used by the health partnerships to strengthen their project work.